Effect of backfat thickness and oestradiol benzoate on reproductive performance of dorper ewes - Hasim, Hazlinda (2017)
Application of oestrus synchronisation had been implemented widely in order to improve farm husbandry. However, information regarding application of intravaginal pessary FGA in sheep especially for Dorper breed reared in Malaysia is lacking. In addition, backfat thickness will be examined to have a better picture on the oestrus synchronisation of sheep production. Two experiments were carried out in this study, the first experiment consisted of 34 Dorper crosses ewes, randomly allocated into three groups where all ewes received intravaginal pessary FGA with Corn oil (CO; n=11), low doses OB (LOB; n=11) and high doses OB (HOB; n=12). A day before pessary removal, 1 ml of PG was injected all ewes regardless of their treatment. Natural mating and oestrus signs observation was conducted using four rams (alternate) after 24 h post pessary removal and OB injection. Results showed 100% of ewes in LOB and HOB groups had oestrus within 60h observation while only 36.36% of ewes in CO group. Meanwhile, standing of oestrus in both LOB and HOB groups shown shorter interval compared to CO group. In second experiment, two factors that are backfat thickness (BFT) and OB doses was analysed with factorial design. This experiment consisted of 71 ewes allocated to two BFT (Thin: Tn=37; Thick: Tk=34) and three doses of OB (Corn oil: CO=25; Low dose of OB: LOB=24 and High dose of OB: HOB=22). Synchronisation protocols were same as previous experiment. Results of oestrus observation showed that there is no interaction between BFT and OB doses, thus main factors was analysed separately. Group that received LOB and HOB had earlier onset of oestrus (LOB=24.5±0.2 h; HOB=26.1±2.1 h) and standing of oestrus (LOB=26.8±1.2; HOB=31.2±2.6 h) compared to CO group (onset of oestrus=39.4±2.6 h; standing of oestrus=44.6±2.3 h). The mean concentration of P4 after 24 h of post pessary removal in all groups showed no significant difference (p>0.05). There was no significantly different (p>0.05) on the pregnancy rate among the groups. There was an interaction between BFT and OB doses for the lambing rate. Ewes that received CO and Tk had the highest (50%) lambing rate compare to other groups. The concentration of leptin between Tn and Tk showed no significant different (p>0.05) during oestrus synchronisation. As conclusion, regardless of OB doses able to synchronised ewes. Further research on BFT is needed to determine best parameter during oestrus synchronisation.